Factors Contributing to Speaking Anxiety: A Case Study of Pre-Service English Teachers - Afrianto Daud; Fakhri Ras; Novitri Novitri; Clara Putri Audia (Journal of Educational Sciences, 2019)
This study is aimed at finding out the level of speaking anxiety experienced by a group of pre-service English teachers at a university in Indonesia and investigating the factors contributing to their speaking anxiety. Using cluster random sampling, this mixed-method research took 30 pre-service English teachers from the same class as the research participants. The data were collected through questionnaires and semi-structured interviews. The questionnaires were adapted from FLCAS (Foreign Language Classroom Anxiety Scale) designed by Horwitz et al (1986). The result of the questionnaire shows that the students’ speaking anxiety is overall in the mildly anxious level. It was identified that there were six students (20%) in the level of very anxious, seven students (23%) in the level of anxious, 14 students (47%) in the mildly anxious level, one student (3%) in the relaxed level, and two students (7%) in the very relaxed level. The interview data indicated that the anxiety was likely because of several inter-related factors: social, linguistic, and personal factors. The social factors include fear of making mistake, feeling under pressure dealing with people, afraid of negative evaluation by teachers, worrying of losing face; the linguistic factor relates to students’ lack of English ability (grammatical issues, proper pronunciation, and vocabulary). While from the personal factor deal with issues such as low motivation and and family problems.